Improving fruit and vegetable intake and production in Tanzania: An evaluation of the FRESH end-to-end approach - Bliznashka, Lilia; Kumar, Neha; Kinabo, Joyce; Mwombeki, Wiston; Hess, Sonja; Marshall, Quinn; Azupogo, Fusta; Olney, Deanna K. (International Food Policy Research Institute, 2023)
Poor diets are a primary cause of malnutrition and the leading cause of disease worldwide. Improving diets, including increasing fruit and vegetable (F&V) intake, could save one in five lives annually. Micronutrients are essential for health; those obtained from F&Vs have a lower environmental footprint than those obtained from other foods making F&Vs essential to sustainable healthy diets. Globally, F&V intake is below recommended levels. However, the extent and nature of the problem is poorly understood due to insufficient data on dietary intake and food environments, especially in low- and middle-income countries.